Preparation and investigation of the heat transfer properties of a novel nanofluid based on graphene quantum dots. (1st December 2017) - Ettefaghi, Ehsanollah; Ghobadian, Barat; Rashidi, Alimorad; Najafi, G.; Khoshtaghaza, Mohammad Hadi; Pourhashem, Sepideh
Graphical abstract: Highlights: Low cost and environmentally friendly nanofluids, which leads to energy saving. High stability of graphene quantum dot nanofluids without any surfactants. Thermal conductivity and convection heat transfer coefficients were investigated. Abstract: In the present research, the biocompatible graphene quantum dots were used to prepare heat transfer nanofluids for the first time. Graphene quantum dots are a new generation of carbon nanoparticles capable of being synthesized from biodegradable and non-toxic resources. In this research, graphene quantum dots were produced by hydrothermal method using citric acid and urea as precursor. Nanofluid samples were synthesized based on car radiator coolant and graphene quantum dots at very low concentrations including 100, 200, 500, and 1000 ppm. One of the advantages of the graphene quantum dots was their long-term stability within the base fluid without using any chemical surfactants. In order to investigate the nanofluids' heat transfer properties, thermal conductivity (k) and convection heat transfer (h) coefficients of the samples were measured. The results for 100 ppm concentration indicated 5.2% and 17% improvement of k and h, compared to the base fluid, respectively. Further, the results demonstrated that the nanofluids containing graphene quantum dots had better stability and performance at low concentrations. Thus, it can be concluded that heat transfer nanofluids based on graphene quantum dots not only reduce probable environmental risks, but also are economically appropriate options for industrial applications; leading to reducing the energy consumption.